Analisis Kinerja Perawatan Bulanan (P1,P3,P6) Dipo KRL Depok - Purwono, Agung; Muhardono, Muhardono; Ryanto, Azhar Hermawan (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2018)
Monthly Maintenance Depok Commuter Line Dipo is a place of care that forms inspection, preparation, storage, maintenance, and repair of rings counted monthly with regular maintenance, where P1 (maintenance every 1 month), P3 (maintenance every 3 months), and P6 (Treatment every 6 boasts). To support Commuter Line maintenance activities, the availability of spare parts / components, quantity and quality of human resources, work equipment, inspection equipment, location, conditions and supporting facilities are sufficient to facilitate maintenance. In conducting maintenance, Depok Commuter Line Dipo Monthly Maintenance has problems, including lack of maintenance equipment and maintenance personnel in the dipo are still lacking, both in terms of quality and quantity. To overcome this problem the method used is to identify the needs of the facility based on the MI (Maintenance Instructions) as a guide in carrying out maintenance and calculate the needs of employees both in number and quality or competence that must be owned by maintenance personnel. From the results of the analysis of the existing problems it can be concluded that the completeness of maintenance facilities in the form of work equipment is still damaged such as compressors and battery changers, lifting jacks, hydraulic jacks, and monthly manure Dipo KRL Depok still needs 24 additional maintenance personnel, and there are 19 People who have not yet participated in functional training competencies. Therefore, it is necessary to add work equipment facilities and increase human resources, as well as improve the quality and quantity of human resources to improve the performance of Depok Commuter Line Dipo Monthly Maintenance